Current global development trends and their impact on the educational and economic systems - Gapsalamov, Almaz Rafisovich; Vasilev, Vladimir Lvovich; Bochkareva, Tatyana Nikolaevna; Akhmetshin, Elvir Munirovich (Linguistics and Culture Review, 2021)
We live in a period of rapid transformations of public institutions caused by the greater momentum of many social, economic, political and technological processes. In this paper, both general and special scientific research methods are used. An expert approach, a content analysis method, a sociological survey, and statistical tools for processing the results were used as special methods. We also conducted an analysis of empirical materials based on the results of a survey of expert groups: university students and lecturers, business representatives and civil servants. Results: The contradictions in the development of the world economy were identified. Along with globalization, there is a tendency towards anti-globalization as cultural differences create greater distance between nations. Another reason for the disintegration of the world’s educational and economic systems is the coronavirus. All the abovementioned conditions have led to an increasing role of digital technologies in education and the economy. However, there are certain contradictions in this process as well. Distance education allows for the exchange of knowledge regardless of geographic location and national boundaries.